2015
DOI: 10.1155/2015/247680
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Study of Chiari Network and the Remnant of Left Venous Valve in the Interior of Right Atrium

Abstract: Chiari network occurs due to incomplete resorption of right valve of sinus venosus. It is often noticed as fenestrated membranous structure or reticular network like structure in the valve of inferior vena cava and coronary sinus. The remnant of left venous valve is observed as trabeculae over the fossa ovalis. The incidence of Chiari network and the remnant of left venous valve were studied in 80 cadaveric hearts utilized for teaching the undergraduates. The right atrium was opened anterior to sulcus terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Early in the human heart development, the left sinus venous valve is fused with the septum primum and becomes part of the interatrial septum [ 18 ]. However, if the left sinus venous valve fuses incompletely with the right aspects of the interatrial septum complex, remnants derived from the left sinus venous valve can present in adults as a thin fenestrated membrane or a trabecular membranous structure overlying the surface of the fossa ovalis [ 9 , 18 ]. Klimek-Piotrowska et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early in the human heart development, the left sinus venous valve is fused with the septum primum and becomes part of the interatrial septum [ 18 ]. However, if the left sinus venous valve fuses incompletely with the right aspects of the interatrial septum complex, remnants derived from the left sinus venous valve can present in adults as a thin fenestrated membrane or a trabecular membranous structure overlying the surface of the fossa ovalis [ 9 , 18 ]. Klimek-Piotrowska et al .…”
Section: Discussionmentioning
confidence: 99%
“…Klimek-Piotrowska et al reported four variations of fossa ovalis anatomy in humans, one of which was a net-like formation within the fossa ovalis that occurs in 7.4% of -14-humans [11]. In addition, the presence of remnants of the left sinus venous valve as a membranous or trabecular membranous structure over the fossa ovalis or the interatrial septum has been reported in 7.5% of humans [9].…”
Section: -12-mentioning
confidence: 99%
“…It has been previously reported that this network is rarely associated with thromboemboli or thrombus formation. CAN usually has a specific shape with many fenestrations in its wall; however, it can also present in a cystic or cord-like shape or a diverticulum 7,8…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of Chiari network in a more recent study involving 80 cadaveric hearts was 3.75%. 12 Another explanation behind the varying prevalence may be the criteria used for defining Chiari network. All structures found in the right atrium in relation to the IVC or coronary sinus is not well visualized, especially in imaging study.…”
Section: Original Articlementioning
confidence: 99%